Design, Development and Characterization of Verapamil Hydrochloride Pulsincap: In Vitro and In Vivo - Kumar, K. Kranthi (Asian Journal of Pharmaceutics (AJP), 2025)
In this present study, design and development, of pulsatile capsule for the timed release of verapamil hydrochloride (HCl), utilizing the pulsincap method for irregular heartbeats. Materials and Methods: Using hydroxy propyl methyl cellulose (HPMC), E15 sugar spheres were sealed. The verapamil HCl was sprayed on sugar spheres using Fluidized Bed (bottom spray) technology. By using FBP HPMC E15 and polymeric solution of cross-Carmellose Sodium also coated a layer on sugar spheres. The formaldehyde-treated 0-sized capsules filled with coated pellets and sealed with 1:1 of HPMC K4 and lactose as a plug. Results and Discussion: The Eudragit L100 was used to release the drug in an extended release. The in vitro drug release was conducted using pH 7.4 phosphate buffer for 17 h with the cumulative percentage release from 99.827%. The formulation V7, which demonstrated 99.827% drug release at 17 h with a 5-h lag time, was identified as the optimized formulation. The in vivo Pharmacokinetic and dynamic studies were conducted in the rabbit model and estimated. The Cmax54.62 ± 0.42 ng/mL, t1/2 8.54 ± 0.013 h, and AUC0-α 944.8 ± 2.07 ng/mL. It was observed that there is a significant difference (P < 0.05) between the pharmacokinetic parameters of the oral solution and pellets of verapamil HCl. Conclusion: A significant lag time of V7 is shown in plasma concentration when compared with the oral solution. The formulation has successfully demonstrated programmed pulsatile release over a 12-h period, aligning with the requirements of Pulsincap drug delivery.